Legal Position Between Narcotics Addicts and Narcotics Abusers in the Perspective of Law Number 35 of 2009 Concerning Narcotics - Munir, Miftahul; Riswadi, Riswadi; Isretno Israhadi, Evita (Jurnal Indonesia Sosial Sains, 2023)
In the overall set of laws in Indonesia, opiates misuse is qualified as a wrongdoing in the opiates area which is controlled in Regulation no. 35 of 2009 concerning Opiates. Opiates wrongdoing is viewed as a type of wrongdoing that has serious ramifications for the eventual fate of this country, obliterating life and the future, particularly for the more youthful age. As indicated by Article 127 passage (1) Regulation no. 35 of 2009, Each individual who mishandles Opiates Classification I for himself will be rebuffed with detainment for a limit of 4 (four) years; Each individual who manhandles Opiates Classification II for himself will be rebuffed with detainment for a limit of 2 (two) years; and Each victimizer of Opiates Class III for himself will be rebuffed with detainment for a limit of 1 (one) year. Concerning what is implied by victimizers are individuals who use opiates without privileges or are illegal. The Opiates Regulation plans to: Guarantee courses of action for clinical and social restoration endeavors for opiates victimizers and fiends", be that as it may, Article 54 of the Law states "Opiates Junkies and Casualties of Opiates Victimizers are expected to go through clinical recovery and social recovery". In light of Article 54, the right of victimizers to get recovery isn't perceived. Moreover, victimizers who get recovery ensures under 4 Regulation no. 35 of 2009, however in Article 127 victimizers are created subjects who can be sentenced and lose their recovery freedoms except if they can be demonstrated or shown to be survivors of opiates. Demonstrating that opiates victimizers are survivors of opiates is a troublesome matter since it should be seen from the start that opiates clients use opiates. Likewise, it is important to demonstrate that opiates clients while utilizing opiates are in a state of being convinced, deceived, misdirected, constrained, as well as taken steps to utilize opiates.